Comparison of effects of continuous combined transdermal with oral estrogen and oral progestogen replacement therapies on serum lipoproteins and compliance - (:unkn) unknown (My University, 2001)
OBJECTIVE: To compare the effects of transdermal and oral hormone replacement therapy on compliance and serum lipoproteins. DESIGN: A total of 159 naturally menopausal women who received either 0.05 mg transdermal estradiol twice weekly or 0.625 mg oral conjugated estrogen daily, with 2.5 mg oral medroxyprogesterone acetate daily, were retrospectively studied. Continuation with or drop-out from treatment regimens, side-effects and bleeding patterns were recorded during a 2-year follow-up period. Baseline, first-year and second-year serum lipoprotein levels were compared between the two groups. RESULTS: Of the 100 women taking oral estrogen, 28 (28%) had dropped out whereas of the 59 women receiving transdermal estrogen, 17 (28.8%) had dropped out at the end of 2 years. The occurrence of bleeding episodes was the most common reason given for discontinuation in both treatment groups (52.9% in the transdermal group and 35.7% in the oral treatment group). The mean increase in high-density lipoprotein (HDL) level for the first year and second year was 10.2 +/- 3.2% and 31.4 +/- 2.8%, and 13.5 +/- 3.2% and 33.6 +/- 3.6% with oral treatment and transdermal therapy, respectively. The mean decrease in total cholesterol for the first year and second year was 2.9 +/- 1.9% and 14.7 +/- 1.6%, and 5.6 +/- 1.7% and 5.7 +/- 1.6% with oral and transdermal treatment, respectively. Likewise, the mean decrease in low-density lipoprotein (LDL) cholesterol for the first year and second year was 6.2 +/- 2.5% and 18 +/- 2.9%, and 7.9 +/- 3.0% and 15.9 +/- 5.2% with oral and transdermal treatment, respectively. There was no significant difference between groups in any of the lipid parameters. Transdermal treatment decreased triglyceride levels by 33.7 +/- 3.9%, whereas oral estrogen treatment increased triglycerides by 18.6 +/- 4.3% at the end of 2 years. This difference between the two groups was statistically significant (p < 0.0001). CONCLUSION: Continuation of treatment was similarly high at the end of 2 years with both transdermal and oral estrogen treatment. Both treatments changed serum lipids favorably. Nevertheless, triglycerides were increased by oral estrogen but decreased by transdermal treatment at 2 years; this difference between the groups was significant.
Keywords: Female; Humans; Middle Aged; Retrospective Studies; Estrogen Replacement Therapy; Postmenopause; Cholesterol; Administration, Oral; Triglycerides; Administration, Cutaneous; Estrogens; Lipoproteins; Medical Records; Cholesterol, LDL; Patient Compliance; Cholesterol, HDL; Progestins